OPTIMALISASI PENJUALAN PRODUK UMKM MELALUI PENGGUNAAN APLIKASI KEUANGAN DAN PENGENDALIAN PERSEDIAAN - Puspitawati, Lilis; Azhara, Namara Salma (Jurnal Riset Akuntansi, 2024)
Optimizing sales is important in ensuring business continuity. This qualitative study was carried out to find empirical evidence of the effectiveness of financial applications and inventory control in optimizing sales of MSME products assisted by IPEMI, Bandung City, West Java. The use of primary data was collected by distributing questionnaires to 155 MSME managers in the city of Bandung which were carried out randomly using the simple random sampling method. The influence between variables was tested using the SMART PLS 4.0 analysis technique. The findings of this research show that the use of financial applications is very effective in increasing sales volume and has a better effect compared to inventory control. This research also provides important aspects for cafe and restaurant business actors in terms of the need for adequate risk assessments for inventory management, the availability of competent resources in managing financial applications and the need for effective sales procedures so that consumers feel helped in encouraging customers to make product purchase transactions.